Desarrollo de un método analítico para la determinación de plaguicidas organoclorados como modificación de la NOM-021-ZOO-1995 - Rodríguez Valdés, Osvaldo Nicolás; Velázquez Chong, Laura Renné; Soto Alvarado, Sonia del Carmen; Rodríguez Ventura, Guillermo; Sánchez López, Eduardo (Acta Universitaria, 2010)
A new method was developed with a GC/PTV/EI/MSMS system designed for the detection and quantification of 21 organochlorine pesticides in bovine fat: α-BHC, γ-BHC (lindane), β-BHC, δ-BHC, Heptachlor, Aldrin, Heptachlor epoxide, γ-chlordane, α-chlordane, Endosulfan I, p,p’- DDE, Dieldrin, Endrin, Endosulfan II, p,p’-DDD, Endrin aldehyde, p,p’-DDT, Endosulfan sulfate, Methoxychlor and Mirex, as a proposal for technological improvement in complying with the Mexican Official Norm NOM-004-ZOO-1994 based on the extraction methodology specified in the Mexican Official Norm NOM-021-ZOO-1995. A Gas Chromatography system was used with an ion trap analyzer and an automatic flow controller in the MS system’s hardware. Increasing the pressure inside the ion trap with high helium flows to optimize the selection of the precursor ion for each pesticide, and amplifying the signals of the product ions, achieved measurements of MSMS with sensitivity values superior to those of electronic capture detectors (ECD), provided correlation coefficient values of ≥0,990, and recovery values in bovine fat of between 60 % and 120 %, thus satisfying the requirements demanded by the Mexican Official Norm.